(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
Endophytic fungi of the medicinal herb, Ocimum sanctum are believed to possess antifungal activity against pathogenic fungi. Due to the emergence of pathogenic fungi and antibiotic-resistant strains, the search for alternative antimicrobial agents is a need. The present study aimed to evaluate the antifungal activity of endophytic fungi isolated from O. sanctum. Plate-to-plate method, disk diffusion assay, and Scanning electron microscopic (SEM) were employed in this study. The finding revealed that fungal isolates Colletotrichum sp. IBRL OS-39, Aspergillus sp. IBRL OS-65, Muscodor sp. IBRL OS-94 and Muscodor sp. IBRL OS-98 was able to produce volatile compounds with antifungal activity against pathogenic fungi. On the disk diffusion assay, Lasiodiplodia sp. IBRL OS-64, and Muscodor sp. IBRL OS-94 displayed good antifungal activity against test fungi with a diameter of inhibition zone between 9.6±0.6 - 14.3±0.6 mm and 11.2±1.2 - 15.7±0.6 mm, respectively. SEM observations revealed remarkable morphological changes in Candida albicans treated with the dichloromethane extracts of Lasiodiplodia sp. IBRL OS-64 and Muscodor sp. IBRL OS-94 with severe cell damage beyond repair and thus leads to cell death.